Oromandibular Limb Hypogenesis Syndrome Type IIB: Case Report of Hypoglossia-Hypodactyly - Manasa Anand Meundi; Gopakumar R. Nair; Prathima Sreenivasan; A. C. Raj (Case Reports in Dentistry)
Hypoglossia-hypodactyly is a rare congenital anomaly affecting the tongue and the limbs. Hall in 1971 classified it under a complex group of disorders called oromandibular limb hypogenesis syndromes. It is an extremely rare condition with around 40 cases reported in the world literature. The cause of the syndrome is unknown. Some type of intrauterine trauma is the most widely accepted etiology. The characteristic features of the syndrome are hypoglossia, limb anomalies of variable degree, and micrognathia of the mandible. This unique case report of hypoglossia-hypodactyly was observed in a patient with normal mandible. In addition, patient also had pulmonary regurgitation. His parents and other siblings were normal. Positive prenatal history of maternal hyperthermia was obtained suspecting it to be the cause of the syndrome.